การวิเคราะห์ค่าความผันผวนเนื่องจากราคาวัสดุในการกำหนดราคากลางงานก่อสร้างของทางราชการ - สุธี คำแฝด (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Because of unclear meaning of contingency in Thailand construction business, the objective of this research is to perform the simulation of contingency in construction works, by which the simulation model is relevant to the present-day conditions. The methodology in this research are: - 1) to define the meaning of contingency, 2) to create a contingency model to be used in construction process, 3) to study the effects of contingency model in cost estimating. However, the scope of contingency in this paper is focused on construction materials price, that happens during the construction. The result of this research shows that contingency in construction process has a relationship with materials price, construction period, and characteristics of projects. The contingency from this research has a relationship with a characteristic of each projects and relates with the real work condition by no setting contingency as a fixed rate and also set the same rate of contingency in every projects. By using regression method for every project and by separately analyzing cost in construction of each project, it was detected that regression analysis of the model in this research can be well applied in estimating process because the end result of the model has low standard error and variables in the contingency equation can be explained. In this study, analyzed data are collected from only asphaltic concrete roads. Thus, the result or its regression equation can be used as a guideline for any research in the future about those kinds of project. However, a better research can be developed furthermore.